2015
DOI: 10.7897/2230-8407.0611147
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Antimicrobial Activities of Neem and Curry Leaf Extracts and Their Synergistic Effect Against Selected Pathogenic Bacteria and Fungus

Abstract: There is a growing demand today for naturally derived drugs and medicine in place of synthetic drugs that are more commercially available. Such drugs derived from indigenous plants are effective as they contain potent therapeutically active compounds of the plants that show antimicrobial activity against a variety of pathogens that cause common diseases. Such diseases as periodontitis and oral candidiasis are a growing concern these days. This study was undertaken to investigate the antimicrobial activity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
2
3
0
Order By: Relevance
“…This finding is parallel to what Bhuva [3] found where it is better for the individual leaves of M. koenigii and Azadirachta indica (neem leaves) to be used separately for an enhanced antibacterial activity against the bacteria strain such Streptococcus mutans, Streptococcus gordonii, and Pseudomonas aeruginosa. Likewise, it is found that M. koenigii is being slightly selective with respect to the use of leaves it is combined with, against gram-positive bacteria, like in the work conducted by Subramaniam [19].…”
Section: Resultssupporting
confidence: 77%
“…This finding is parallel to what Bhuva [3] found where it is better for the individual leaves of M. koenigii and Azadirachta indica (neem leaves) to be used separately for an enhanced antibacterial activity against the bacteria strain such Streptococcus mutans, Streptococcus gordonii, and Pseudomonas aeruginosa. Likewise, it is found that M. koenigii is being slightly selective with respect to the use of leaves it is combined with, against gram-positive bacteria, like in the work conducted by Subramaniam [19].…”
Section: Resultssupporting
confidence: 77%
“…The weak antifungal properties of these essential oils are in agreement with those reported in literature such as, C. odorata (Kuspradini et al, 2016;Lee and Lee, 2010), E. hortensis (Huish et al, 2014;Yazdanpanah and Mohamadi, 2014), M. koenigii (Bhuva and Dixit, 2015;Kumar et al, 2010). The weak antifungal activity of essential oils in this study can be due to the absence of strong antifungal compounds that include linalool, eugenol and other phenolic compounds as reported in different plant extracts (Campaniello et al, 2010;Tan et al, 2015).…”
Section: Antifungal Activities Of Selected Essential Oilssupporting
confidence: 89%
“…As compared with synthetic drugs, naturally derived drugs are therapeutically active and commercially available [15] . The antimicrobial activity and MIC ranges between 10.00 mg/ml to 100 mg/ml exhibited by aq.…”
Section: Resultsmentioning
confidence: 99%